Investor Expectation Management Strategies through IPO Roadshow and Book-building Processes - Sandopart, Dewa Putu Yohanes Agata L. (Jurnal Ekonomi, Manajemen, dan Bisnis, 2025)
This study explores investor expectation management strategies implemented by issuers and underwriters during the roadshow and book-building process of Initial Public Offerings (IPOs) on the Indonesia Stock Exchange. Employing a qualitative approach with an instrumental case study design, this research analyzes three main issuers representing the technology, consumer, and infrastructure sectors during the 2021-2025 period. Data were collected through in-depth interviews with 24 participants (issuer management, underwriters, institutional investors, and regulators), participant observation at three roadshow sessions, and document analysis of prospectuses and order book data. Thematic analysis yielded six main themes: (1) construction of corporate value narrative through selective framing, (2) two-stage price negotiation reflecting fundamentals and sentiment, (3) management of oversubscription and scarcity perception, (4) iterative feedback mechanisms between stages, (5) strategy differentiation based on issuer characteristics, and (6) implementation challenges and ethical risks. The main findings indicate that small technology companies employ aggressive strategies with the highest underpricing level (28.6%), while large infrastructure companies employ conservative strategies with the lowest underpricing (8.2%). This study confirms and extends Okamoto's (2023) two-step price adjustments model to the Indonesian emerging market context. The novelty lies in the systematic mapping of communication tactics used by management and underwriters in managing heterogeneous investor expectations. Policy implications include recommendations for adopting hybrid IPO auction models and strengthening supervision of selective disclosure practices during roadshows.